Influence of Time to Surgery in Ankle Fractures on the Rate of Complications and Length of Stay – a Multivariate Analysis - Burchard, Rene; Hamidy, Karacan; Pahlkötter, Anke; Soost, Christian; Palm, Michael; Graw, Jan Adriaan; Bouillon, Bertil (Zeitschrift für Orthopädie und Unfallchirurgie, 2019)
Background With an incidence of 9/1000 per year, ankle fracture is one of the most common skeletal injuries. It is currently unclear whether time to surgery affects the complication rate or the hospital length of stay and whether there are confounders in patient characteristics or comorbidities.Material and Methods In a retrospective cohort study (n = 421), the risk of perioperative complications in patients with a primary operative fracture treatment within 6 hours of trauma was compared to a secondary surgical treatment. Furthermore, the influence of patient characteristics and comorbidities was examined in a multivariate regression analysis.Results In comparison to secondary therapy, there was no benefit of a surgical fracture treatment within 6 hours after trauma was detected with regard to the perioperative complication rate or the hospital length of stay. Advanced patient age and severe soft tissue damage were associated with prolonged hospital length of stay but not with an increased rate of local perioperative complications.Conclusion The occurrence of severe local perioperative complications after surgical treatment of an ankle fracture is not associated with the time to surgery or covariates such as patient age or comorbidities. Current German guidelines for ankle fractures recommend surgical treatment within 6 – 8 hours, but these should be re-evaluated in further prospective randomised studies.
Keywords: ankle fracture; time to surgery; complication; length of stay